2018
DOI: 10.1111/deci.12345
|View full text |Cite
|
Sign up to set email alerts
|

A Graph Mining Approach to Identify Financial Reporting Patterns: An Empirical Examination of Industry Classifications

Abstract: This study proposes a quantitative method using the eXtensible Business Reporting Language financial accounting taxonomies to identify firms' common business characteristics and demonstrates that this graph mining approach can effectively identify industry boundaries. The premise of this method is based on the previous findings that financial accounts and the structural semantic information represented in financial statements reveal firms' general business operations and common characteristics if they have sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Furthermore, several studies [2], [9] have suggested that organizations with similar business activities should have similar financial statements. This idea is confirmed by Yang et al [6], where they provide evidence that a company distance metric can effectively identify industry boundaries.…”
Section: Related Workmentioning
confidence: 68%
See 2 more Smart Citations
“…Furthermore, several studies [2], [9] have suggested that organizations with similar business activities should have similar financial statements. This idea is confirmed by Yang et al [6], where they provide evidence that a company distance metric can effectively identify industry boundaries.…”
Section: Related Workmentioning
confidence: 68%
“…One of the drawbacks is that classification systems do not evolve at the same rate as the market conditions, making it difficult to classify new industries [11]. Another drawback is the lack of uniform classification standards, which results in a different company classification depending on the industry classification standard being used [6]. This implies that we cannot merely distinguish organizations based on their size and industry classification.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have used the graph mining technique for data analysis. Yang et al (2009), using eXtensible Business Reporting Language, identified common business characteristics of companies. They showed that graph mining could effectively identify industry boundaries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As advances in computing power enhance the ability of scholars to deal with complex calculations, researchers in information systems have adopted a variety of approaches to classify industries for grouping homogeneous firms (Fang et al, 2013;Chowdhuri et al, 2014;Yang et al, 2019;Xu et al, 2020). Among many academic works related to alternative industry classifications, Hoberg and Phillips (2016) develop the text-based network industry classification (TNIC) derived from the firms' business descriptions of 10-K reports.…”
Section: Introductionmentioning
confidence: 99%